Associations between leptin gene polymorphism and some reproductive traits in Holstein-Friesian dairy cattle : Επίδραση του γονιδίου της λεπτίνης στη γονιμότητα - Kibar, M; Aytekin, İ (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to determine the effect of leptin gene polymorphism and other environmental factors on age of using at first breeding (AUFB; day), age at first calving (AFC; day), service period (SP; day), number of inseminations per conception (NIPC; count), gestation period (GP; day) and calving interval (CI; day). For this purpose, whole blood samples were obtained from the Vena coccygea of 212 head of Türkiye Holstein Friesian dairy cattle reared on a private farm. The Sau3AI restriction enzyme with the PCR-RFLP method was used to determine the polymorphism of 422 base pairs (bp) in the intron 2 region of the leptin gene. The frequencies of the A and B alleles and the AA, AB and BB genotypes were determined to be 0.8821 and 0.1179, and 0.764, 0.236 and 0.000, respectively. There were no animals with the BB genotype in the population. The population of Hostein-Friesian was also at the level of Hardy-Weinberg with regard to the leptin gene (P>0.05). Regarding the highest and the lowest direct heritability were found in the GP (0.33±0.268) and NIPC (0.01±0.118), respectively. For SP (P<0.10), NIPC (P<0.05) and CI (P<0.05) higher values were found in genotype AA cattle than in genotype AB cattle. However, no significant association was found between genotypes and AUFB, AFC, GP, and estimated breeding values (EBVs). As a result, the AB genotype or B allele could be used in selection for SP, NIPC, and CI, but the allele or genotype did not suggest MAS-based selection (marker-assisted selection) for AUFB, AFC, and GP. Also, more research with more animals and genes is needed to increase the effectiveness of selection for reproductive traits in Holstein-Friesian dairy cattle.